Intramolecular ipso-arylative cyclization of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts through merged gold/visible light photoredox catalysis - Bansode, Avinash H.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2017)
A visible-light-promoted merged gold/photoredox catalyzed ipsoarylative cyclization has been reported. For instance, the reaction of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts in the presence of catalytic amounts of [(4-OCH3)C6H4](3)PAuCl and Ru(bpy)(3)(PF6)(2) under irradiation using a 32WCFL bulb gave arylated spirocarbocycles in moderate to good yields.